Progression of vital signs during ambulance transport categorised by a paediatric triage model: a population-based historical cohort study - Vibe Maria Laden Nielsen; Torben Kløjgård; Henrik Bruun; Morten Breinholt Søvsø; Erika Frischknecht Christensen (BMJ Open)
Objectives To examine the severity and progression of acute illness or injury in children using vital signs obtained during ambulance transport and categorised according to a paediatric triage model.Design A population-based historical cohort study using data from prehospital patient medical records linked to a national civil registration database.Setting Emergency medical services providing ground-level transport in a mixed urban–rural region with three hospitals in Denmark.Participants 25 039 events with patients aged <18 years attended by emergency medical services dispatched after a 1-1-2 emergency call during the years 2006–2018.Primary and secondary outcome measures Distribution of the first observed vital signs according to a paediatric triage model: heart rate, Glasgow Coma Score, respiratory rate, oxygen saturation and oxygen treatment, and proportion of patients progressing to a triage score with a lower level of urgency during ambulance transport.Results The proportion of patients with the first observed vital signs outside the normal age-specific range was as follows: 33.6% for heart rate, 15.3% for Glasgow Coma Score, 17.4% for respiratory rate and 37.4% for oxygen saturation regardless of oxygen treatment. The proportion of patients progressing to a triage score with a lower level of urgency during transport varied with age: 146/354 (41.2%) for age 0–2 months, 440/986 (44.6%) for age 3–11 months, 1278/3212 (39.8%) for age 1–2 years, 967/2814 (34.4%) for age 3–7 years and 4029/13 864 (29.1%) for age 8–17 years (p<0.001). One-day mortality was 3.05 deaths per 1000 patient-days (95% CI 2.43 to 3.83).Conclusions One third of the patients’ condition progressed to a triage score with a lower level of urgency during ambulance transport. Vital sign documentation in paediatric patients was incomplete, and educational initiatives should be taken to increase documentation of vital signs, especially in patients aged ≤2 years.